CALCULATION OF AIR IN THE SPACE UNDER THE SIMULTANEOUS ACTION OF GRAVITATIONAL PRESSURE, PRESSURE AND WIND FAN - and and (Municipal economy of cities (Technical science), 2013)
The method of calculating the air in the room with simultaneous action of gravitational pressure, wind pressure and fan. The case when the inlet openings the premises are located at different heights from the floor.